2015
DOI: 10.14486/ijscs226
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Morphological Characteristics on the Situational-Motor Abilities of Sitting Volleyball Players

Abstract: Analysis of the impact of morphological characteristics on situational-motor abilities of sitting volleyball players was applied on the sample of 90 examinees, registered players of Premier League of Bosnia and Herzegovina in sitting volleyball, and among of them it was fifteen representatives of Bosnia and Herzegovina. In this research is applied a set of battery test which contains 23 variables in which 15 variables are of morphological characteristics and the system of 8 variables for assessing situational-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 2 publications
1
8
0
2
Order By: Relevance
“…According to the results of the research, it was reported that the players with longer arm lengths, wider pelvis width and upper arm circumference, and lower abdominal skinfold values have an advantage in application of conditional-motor features and morphological measurements were dominant in sitting volleyball. The findings of that research verify the determinations obtained by Mahmutovic et al [9].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…According to the results of the research, it was reported that the players with longer arm lengths, wider pelvis width and upper arm circumference, and lower abdominal skinfold values have an advantage in application of conditional-motor features and morphological measurements were dominant in sitting volleyball. The findings of that research verify the determinations obtained by Mahmutovic et al [9].…”
Section: Discussionsupporting
confidence: 90%
“…However, although the height of the net is lower, considering the characteristics of the game, since failure to contact either buttocks to the ground is forbidden by rule, we are of the opinion that both upper extremities and upper body height is vital in all parts of the game, particularly in offence and block positions, and they are important criteria in selection of the players. This determination is supported by the research conducted by [9,21].…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations